Grundtvigs billedverden og teologien - Bjerring-Hansen, Mogens (Grundtvig-studier, 1992)
Grundtvig's » Pictureworld« and the theology.Jens Holger Schjørring: Grundtvig's » Pictureworld« - and the church view. Works published by the Grundtvig Society, bd. XXI, 1990. Reviewed by Moges Bjerring-Hansen